Neoliberal Policy of Indonesia’s Agricultural Revitalization - Winarno, Budi (Jurnal Hubungan Internasional, 2016)
This paper discusses Indonesian food agricultural policy, particularly since the Susilo Bambang Yudhoyono (SBY) administration. Influenced by the powers of global political economy, Indonesia has been dictated to practice neoliberal policies, including those in agricultural sector. The government had launched a policy of agricultural revitalization to encourage agricultural productivity through a private involvement. This study concludes that the agricultural revitalization is just a short-term pragmatic policy and serves the neoliberal ideology. It is not solve the major problems of food security and of rural life. What has to be done by the government is a long-term attempt and planning to strengthen the productivity and production of food agriculture and to improve the life of poor peasants in rural areas—the majority of Indonesian population. Essentially, the attempt and planning has to be directed into two basic problems on food security in Indonesia, which are the problem of ‘food access’ and ‘peasant vulnerability’.